if a is equal to 7 x square + 5 x y -9 y square b=-4 x square + xy +5y square comma C is equal to 4 y square - 3 x square - 6 x y then show that a + b + C is equal to zero
Answers
Answered by
7
Answered by
14
Heres your answer mate
a = {7x}^{2} + 5xy - 9 {y}^{2} \\ \
\ b = - 4 {x}^{2} + xy + 5 {y}^{2}![a = {7x}^{2} + 5xy - 9 {y}^{2} \\ \\ b = - 4 {x}^{2} + xy + 5 {y}^{2} \\ \\ c = 4 {y}^{2} - 3 {x}^{2} - 6xy \\ \\ a + b + c \\ \\ 7 {x}^{2} + 5xy - 9 {y}^{2} + ( - 4 {x}^{2} + xy + 5 {y}^{2} ) + \\ (4 {y}^{2} - 3 {x}^{2} - 6xy) \\ \\ = (7 {x}^{2} - 4 {x}^{2} - 3 {x}^{2} ) - 9 {y}^{2} + 5 {y}^{2} + 4 {y}^{2} + (5xy + xy \\ - 6xy) \\ \\ = 0 {x}^{2} + 0 {y}^{2} + 0xy \\ \\ = 0 a = {7x}^{2} + 5xy - 9 {y}^{2} \\ \\ b = - 4 {x}^{2} + xy + 5 {y}^{2} \\ \\ c = 4 {y}^{2} - 3 {x}^{2} - 6xy \\ \\ a + b + c \\ \\ 7 {x}^{2} + 5xy - 9 {y}^{2} + ( - 4 {x}^{2} + xy + 5 {y}^{2} ) + \\ (4 {y}^{2} - 3 {x}^{2} - 6xy) \\ \\ = (7 {x}^{2} - 4 {x}^{2} - 3 {x}^{2} ) - 9 {y}^{2} + 5 {y}^{2} + 4 {y}^{2} + (5xy + xy \\ - 6xy) \\ \\ = 0 {x}^{2} + 0 {y}^{2} + 0xy \\ \\ = 0](https://tex.z-dn.net/?f=a+%3D++%7B7x%7D%5E%7B2%7D++%2B+5xy+-+9+%7By%7D%5E%7B2%7D+%5C%5C++%5C%5C+b+%3D++-+4+%7Bx%7D%5E%7B2%7D++%2B+xy+%2B+5+%7By%7D%5E%7B2%7D++%5C%5C++%5C%5C+c+%3D+4+%7By%7D%5E%7B2%7D++-+3+%7Bx%7D%5E%7B2%7D++-+6xy+%5C%5C++%5C%5C+a+%2B+b+%2B+c+%5C%5C++%5C%5C+7+%7Bx%7D%5E%7B2%7D++%2B+5xy+-+9+%7By%7D%5E%7B2%7D++%2B+%28+-+4+%7Bx%7D%5E%7B2%7D++%2B+xy+%2B+5+%7By%7D%5E%7B2%7D+%29+%2B++%5C%5C+%284+%7By%7D%5E%7B2%7D++-+3+%7Bx%7D%5E%7B2%7D++-+6xy%29+%5C%5C++%5C%5C+%3D++%287+%7Bx%7D%5E%7B2%7D++-+4+%7Bx%7D%5E%7B2%7D++-+3+%7Bx%7D%5E%7B2%7D+%29+-+9+%7By%7D%5E%7B2%7D++%2B+5+%7By%7D%5E%7B2%7D++%2B+4+%7By%7D%5E%7B2%7D++%2B+%285xy+%2B+xy+%5C%5C++-+6xy%29+%5C%5C++%5C%5C+%3D++0+%7Bx%7D%5E%7B2%7D++%2B+0+%7By%7D%5E%7B2%7D++%2B+0xy+%5C%5C++%5C%5C++%3D+0)
Hence the answer is 0
Hope it Helps!!..
a = {7x}^{2} + 5xy - 9 {y}^{2} \\ \
\ b = - 4 {x}^{2} + xy + 5 {y}^{2}
Hence the answer is 0
Hope it Helps!!..
Similar questions